2019
DOI: 10.1111/vde.12729
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of different sets of criteria in diagnosing canine atopic dermatitis applied to a population of 250 dogs seen in a veterinary teaching hospital

Abstract: Background -Different sets of criteria are available in veterinary dermatology for the diagnosis of canine atopic dermatitis (cAD); there are limited data to assess their reliability.Hypothesis/Objectives -The aim of this study was to assess the discriminative and predictive ability of four sets in diagnosing cAD in a population of dogs with different skin diseases.Animals -Two hundred and fifty dogs examined in the dermatology unit of a veterinary teaching hospital.Methods and materials -Dogs were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The International Committee for Allergic Diseases in Animals (ICADA) has outlined three ways in which a CAD diagnosis can be made by trained practitioners: (1) elimination of similar skin conditions through formal examination and work-up; (2) interpretation of clinical history and features based on diagnostic criteria sets; and (3) allergy testing for confirmation and allergen identification [1]. Multiple diagnostic criteria sets exist to aid in the interpretation of clinical features associated with CAD; however, Brément et al compared Willemse [145], Prélaud [146], and Favrot (both set 1 and set 2) [88] and demonstrated that when used in isolation all criteria sets were unreliable [147]. Thus, it is recommended that all three diagnostic approaches outlined by ICADA are used in combination for a more accurate assessment, which was not possible in the present investigation [1,11,147].…”
Section: Discussionmentioning
confidence: 99%
“…The International Committee for Allergic Diseases in Animals (ICADA) has outlined three ways in which a CAD diagnosis can be made by trained practitioners: (1) elimination of similar skin conditions through formal examination and work-up; (2) interpretation of clinical history and features based on diagnostic criteria sets; and (3) allergy testing for confirmation and allergen identification [1]. Multiple diagnostic criteria sets exist to aid in the interpretation of clinical features associated with CAD; however, Brément et al compared Willemse [145], Prélaud [146], and Favrot (both set 1 and set 2) [88] and demonstrated that when used in isolation all criteria sets were unreliable [147]. Thus, it is recommended that all three diagnostic approaches outlined by ICADA are used in combination for a more accurate assessment, which was not possible in the present investigation [1,11,147].…”
Section: Discussionmentioning
confidence: 99%
“…The International Committee for Allergic Diseases of Animals (ICADA) classified canine atopic dermatitis (cAD) as a genetically predisposed inflammatory and pruritic allergic skin disease with many possible manifestations; several clinical features are associated with IgE antibodies that are most frequently directed against environmental allergens [ 1 , 2 ]. cAD is subjective by the interaction of both, genetic and environmental factors, by abnormalities of the immune system, by its interaction with the nervous system and by defects in the epidermal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary dermatology practice, canine atopic dermatitis (AD) is a multifactorial allergic disease that affects up to 27% of dogs; it is associated with immune and abnormal skin barrier dysfunction and it is one of the primary causes of pruritus (1). Many pharmacological options for its treatment already exist; however, due to elevated costs, side effects, and/or a long lag phase, treatments based on natural compounds are constantly being developed (2).…”
Section: Introductionmentioning
confidence: 99%